The Effect of Product Quality on Purchase Decision Mediated by Brand Image in Zara Women’s Bag Consumers - Wiwin Arifin; Marsudi Marsudi; Rahmad Wijaya (Universitas Muhammadiyah Malang, 2022)
This study examines the effect of product quality on purchasing decisions with the brand image as a mediating variable. The research was conducted in Tunjungan Plaza, Galaxy Mall, and Pakuwon Mall with a total sample of 150 respondents of Zara Women’s consumers. The data collection technique in this study used an online questionnaire. The data analysis technique in this study uses partial least squares using Smart PLS software. The results of the partial least squares (PLS) analysis show that product quality has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions, and product quality has a positive and significant effect on purchasing decisions.